(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
This paper will give the meaning of the CSR and recognize some of the factors that led to the emergence of corporate social responsibility. It will also discuss the importance of corporates setting up corporate social responsibility projects, and the impact these have on their performance and society as well.